Analysis of Vitamin D Levels in Vaccinated and Non Vaccinated Pregnant Women with Covid-19 - Muhammad Ahmad, Saira Bajwa, Ghazala, Muhammad Faisal, Bushra Mehmood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to examine the levels of vitamin D in pregnant women who have been vaccinated and those who have not been vaccinated. Study Design: Comparative/Observational study Place and Duration: CMH Bahawalpur.Jun-2019-Feb 2020 Methods: A total of 106 cases of coronavirus illness in pregnant women were reported. Permission to collect detailed demographic information such as age, gestational age, parity, and body mass index was obtained by written informed permission. Women were mostly between the ages of 18 and 42. Patients were grouped into two distinct categories. Group A included 53 people who had vaccinations, whereas group B included 53 women who had not received vaccinations. Serum 25-hydroxy vitaminD3 [25 (OH) D3] levels were measured in all individuals. The levels of vitamin D insufficiency in the two groups were compared. Vitamin D sufficiency was defined as a blood level of >30ng/ml. The full dataset was analyzed by using SPSS 24.0. Results: In group number of primigravida was 24 (45.2%) and in group II 26 (49.1%) cases were. Frequency of vitamin D deficiency was lower in group I 44 (83.01%) patients as compared to group II in 50 (94.3%) cases. In group I, severe deficiency (<10ng/ml) was found in 10 (18.9%), deficiency (10-20ng/ml) were found in 14 (26.4%) and not-sufficient (20-30ng/ml) were in 20 (37.7%) while in group II severe deficiency (<10ng/ml) was found in 15(28.3%), frequency of deficient patients (10-20ng/ml) was 17 (32.1%) and not-sufficient cases (20-30ng/ml) were 18 (33.9%). In group I deficient vitamin D serum levels was 16.03±2.42 and in group II was 13.14±8.41. Conclusion: According to the findings of this research, vitamin D insufficiency is more common in pregnant women who have not been vaccinated and is more likely to occur in these women, as well as in non-vaccinated patients who do not have low blood levels.